Ammonia volatilization loss from surface placed urea-treated POME pellets - Hussin, Aminuddin (Universiti Pertanian Malaysia Press, 1995)
Ammonia volatilization loss from urea applied to inland Malaysian soils can be as high as 50% of the nitrogen (N) applied. The high pH of the microsites developed upon urea hydrolysis results in NH + being unstable leading to (NH3) volatilizing. In this study acidified POME (palm oil mill effluent) was matrixed with urea and pelletized with the objective of providing lower pH of the microsite during urea hydrolysis. The high cation exchange capacity (CEC) of the POME could also increase the H-buffering and sites for NH4+ adsorption. Results show that urea-30 % POME acidified was able to reduce NH3 volatilization loss to 8% compared with 30 % of the urea-only pellets. Reduction in NH3 volatilization loss was directly correlated with increase in the POME content in pellets. The higher the POME, the lower NH3 volatilized. CEC and H-buffering are properties of POME that help reduce NH3 volatilization loss. The high CEC adsorps NH+ from the hydrolysis of urea and the H-buffering reduces the pH of the microsites.